Förster resonance energy transfer and energy cascade with a favorable small molecule in ternary polymer solar cells. (1st December 2016) - Xing, Shen; Wang, Hanyu; Zheng, Yifan; Yu, Junsheng
Highlights: High PCE of 8.03% with a simultaneous enhancement of JSC and FF is achieved. Optical, electrical and morphological properties of ternary system are investigated. Incorporation of Rubrene increases charge transfer and energy transfer efficiency. Rubrene increases photoconductive carriers and suppressed bimolecular recombination. Abstract: In this work, through adding a fluorescent small molecule, Rubrene, in the active layer, a highly efficient ternary polymer solar cell (PSC) is obtained. By modifying the ratio of Rubrene in poly(4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2-b:4, 5-b0]dithiophene-2, 6-diyl3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3, 4-b]thiophenediyl) (PTB7):[6, 6]-phenyl C71-butyric acidmethyl ester (PC71 BM) blends, the short circuit current and fill factor are simultaneously enhanced, resulting in a 21.7% improvement in power conversion efficiency from 6.60% to 8.03%. Improved photovoltaic performance of ternary PSCs is mainly due to enhanced charge transportation by appropriate energy cascade alignment and strong Förster resonance energy transfer from Rubrene to PTB7. Moreover, the appropriate location of Rubrene in the ternary blends optimizes the blend morphology. Furthermore, the impedance spectroscopy results indicate that the incorporation of Rubrene can increase the number of photoconductive carriers and suppress the bimolecular recombination.